Molecular Mechanisms of Action of FSH - Casarini, Livio; Crépieux, Pascale (Frontiers in Endocrinology, 2019)
The glycoprotein follicle-stimulating hormone (FSH) acts on gonadal target cells, hence regulating gametogenesis. The transduction of the hormone-induced signal is mediated by the FSH-specific G protein-coupled receptor (FSHR), of which the action relies on the interaction with a number of intracellular effectors. The stimulatory Gαs protein is a long-time known transducer of FSH signaling, mainly leading to intracellular cAMP increase and protein kinase A (PKA) activation, the latter acting as a master regulator of cell metabolism and sex steroid production. While in vivo data clearly demonstrate the relevance of PKA activation in mediating gametogenesis by triggering proliferative signals, some in vitro data suggest that pro-apoptotic pathways may be awakened as a “dark side” of cAMP/PKA-dependent steroidogenesis, in certain conditions. P38 mitogen-activated protein kinases (MAPK) are players of death signals in steroidogenic cells, involving downstream p53 and caspases. Although it could be hypothesized that pro-apoptotic signals, if relevant, may be required for regulating atresia of non-dominant ovarian follicles, they should be transient and counterbalanced by mitogenic signals upon FSHR interaction with opposing transducers, such as Gαi proteins and β-arrestins. These molecules modulate the steroidogenic pathway via extracellular-regulated kinases (ERK1/2), phosphatidylinositol-4,5-bisphosphate 3-kinases (PI3K)/protein kinase B (AKT)-, calcium signaling and other intracellular signaling effectors, resulting in a complex and dynamic signaling network characterizing sex- and stage-specific gamete maturation. Even if the FSH-mediated signaling network is not yet entirely deciphered, its full comprehension is of high physiological and clinical relevance due the crucial role covered by the hormone in regulating human development and reproduction.